A hydrogen-rich early Earth atmosphere - Tian, F.; Toon, O. B.; Pavlov, A. A.; De Sterck, H. (Science, 2005)
We show that the escape of hydrogen from early Earth's atmosphere likely occurred at rates slower by two orders of magnitude than previously thought. The balance between slow hydrogen escape and volcanic outgassing could have maintained a hydrogen mixing ratio of more than 30%. The production of prebiotic organic compounds in such an atmosphere would have been more efficient than either exogenous delivery or synthesis in hydrothermal systems. The organic soup in the oceans and ponds on early Earth would have been a more favorable place for the origin of life than previously thought.
Tian, FengToon, Owen BPavlov, Alexander ADe Sterck, HengResearch Support, U.S. Gov't, Non-P.H.S.2005/04/09 09:00Science. 2005 May 13;308(5724):1014-7. Epub 2005 Apr 7.